Epidural Analgesia after Rib Fractures. Issue 10 (October 2015) - Zaw, Andrea A.; Murry, Jason; Hoang, David; Chen, Kevin; Louy, Charles; Bloom, Matthew B.; Melo, Nicolas; Alban, Rodrigo F.; Margulies, Daniel R.; Ley, Eric J.
Pain associated with rib fractures impairs respiratory function and increases pulmonary morbidity. The purpose of this study was to determine how epidural catheters alter mortality and complications in trauma patients. We performed a retrospective study involving adult blunt trauma patients with moderate-to-severe injuries from January 1, 2004 to December 31, 2013. During the 10-year period, 526 patients met the inclusion criteria; 43/526 (8%) patients had a catheter placed. Mean age of patients with epidural catheter (CATH) was higher compared with patients without epidural catheter (NOCATH) (54 vs 48 years, P = 0.021), Injury Severity Score was similar (26 CATH vs 27 NOCATH, P = 0.84), and CATH had higher mean rib fractures (7.4 vs 4.1, P < 0.001). Mortality was lower in CATH (0% vs 13%, P = 0.006). Deep vein thrombosis (DVT) rate was higher in CATH (12% vs. 5%, P = 0.036). After regression analysis, we found catheter placement to be a predictor for DVT (adjusted odds ratios 2.80, P = 0.036). Our center noted increased use of epidural catheters in patients who present with moderate-to-severe injuries. Patients with catheters were older and had a mean of 7.4 ribs fractured. The epidural cohort had longer hospital LOS and decreased mortality. In contrast to other studies, DVT rates were increased in patients who received epidural catheters.